EVALUATION OF SOME FUNGICIDES, BOTANICALS AND ESSENTIAL OILS AGAINST THE FUNGUS COLLETOTRICHUM FALCATUM CAUSING RED ROT OF SUGARCANE - BHARDWAJ, NIKHIL; R. K. SAHU, (The Bioscan, 2014)
Different botanicals, fungicides and essential oils were evaluated in vitro against Colletotrichum falcatum. Amongst botanicals evaluated, it was found that at 15 per cent concentration, maximum inhibition in mycelial growth (92.59%) was recorded in Ocimum followed by Turmeric (79.25%), Ginger (75.92%), Onion (72.41) and minimum inhibition in mycelial growth (64.44%) was recorded in Garlic. Among five essential oils at 10µL concentration, complete inhibition in mycelial growth was recorded by Peppermint oil and Mentha oil, followed by Geranium oil (75.83%), Patchouli oil (70.00%) while minimum inhibition in mycelial growth was recorded in Palmaroza oil (63.89%). Out of four fungicides, at 20 ppm concentration, Bavistin showed complete inhibition of mycelial growth of the test fungus followed by Folicur (88.89 %), Contaf (81.89%) while least inhibition was by Tilt (80.78%).